Texting for Help: Processes and Impact of Text Counseling with Children and Youth with Suicide Ideation. Issue 5 (23rd November 2018) - Sindahl, Trine N.; Côte, Louis‐Phillippe; Dargis, Luc; Mishara, Brian L.; Bechmann Jensen, Torben
Abstract : Objective: To explore: (1) how children contacting a child helpline with suicide ideation differ from children discussing other topics, (2) whether text messaging effectively helps, and (3) which counselor behaviors are most effective. Method: Of 6, 060 text sessions at the Danish national child helpline, 444 concerned suicidality, of which the 102 sessions that included self‐rated, end Session ratings were selected for content analysis. Results: Twenty‐six percentage of suicidal children had severe suicidality. The suicide sample had significantly more girls, was older than the nonsuicide sample, and more often recontacted the helpline in the 2 weeks prior to follow‐up. 35.9% of suicidal children felt better immediately and over half ended the session with a plan of action. At follow‐up, 23.9% of suicidal children reported feeling better; however, 37.0% reported feeling worse. Talking about emotions, expressing empathy, and encouraging the child to talk to someone were associated with positive impacts. Setting boundaries was associated with negative impacts. Conclusions: Texting with suicidal children can be helpful, but should be considered a first step toward obtaining more sustainable help. Research is needed to determine how to better help children who felt worse or did not improve in the 2 weeks after contacting the helpline. Suggestions to further training of counselors are discussed.